Kinetic modeling and half life study on bioremediation of crude oil dispersed by Corexit 9500 - Zahed, M.A. (Elsevier, 2011)
Hydrocarbon pollution in marine ecosystems occurs mainly by accidental oil spills, deliberate discharge of ballast waters from oil tankers and bilge waste discharges; causing site pollution and serious adverse effects on aquatic environments as well as human health. A large number of petroleum hydrocarbons are biodegradable, thus bioremediation has become an important method for the restoration of oil polluted areas. In this research, a series of natural attenuation, crude oil (CO) and dispersed crude oil (DCO) bioremediation experiments of artificially crude oil contaminated seawater was carried out. Bacterial consortiums were identified as Acinetobacter, Alcaligenes, Bacillus, Pseudomonas and Vibrio. First order kinetics described the biodegradation of crude oil. Under abiotic conditions, oil removal was 19.9% while a maximum of 31.8% total petroleum hydrocarbons (TPH) removal was obtained in natural attenuation experiment. All DCO bioreactors demonstrated higher and faster removal than CO bioreactors. Half life times were 28, 32, 38 and 58 days for DCO and 31, 40, 50 and 75 days for CO with oil concentrations of 100, 500, 1000 and 2000 mg/L, respectively. The effectiveness of Corexit 9500 dispersant was monitored in the 45 day study; the results indicated that it improved the crude oil biodegradation rate.